Comparison of three different bulk-filling techniques for restoring class II cavities: μCT, SEM-EDS combined analyses for margins and internal fit assessments. (December 2021) - Putignano, Angelo; Tosco, Vincenzo; Monterubbianesi, Riccardo; Vitiello, Flavia; Gatto, Maria Laura; Furlani, Michele; Giuliani, Alessandra; Orsini, Giovanna
Abstract: Objective: Evaluation of the behavior of three different bulk-filling techniques in terms of internal adaptation and external marginal sealing for restoring class II cavities. Methods: Fifteen extracted sound molar teeth were used. Two standardized class II mesio/disto-occlusal (MO/DO) slot cavities, 4 mm long, 4 mm wide and 3 mm deep were prepared in each tooth, obtaining n=30 cavity preparations. The cavities were randomly assigned into three groups (n=10 per group) according to three bulk filling techniques: Bulk Traditional (BT), Bulk&Go (BG) and Bulk&Flow (BF). The teeth were analyzed by scanning electron microscopy (SEM) to investigate the external marginal seal. Thereafter, the chemical composition of tooth-restoration interface was analyzed by energy-dispersive X-ray spectroscopy (EDS). Complementary information to the SEM and EDS were obtained by micro-computed tomography (μCT) to assess the internal fit. Results: SEM analysis showed a proper external marginal seal for all groups tested as confirmed by the EDS investigation, highlighting the presence of adhesive layer at the tooth-restoration interface. The internal marginal adaptation by means of μCT analysis revealed gaps formation at the tooth–restoration interface only for BT group, while an intimate contact free of gaps were found in the other two groups. Moreover, in BT and BF groups voids were present within the restoration. Significance: BG and BF techniques can be considered as reliable alternatives to BT technique, as they simplify the class II restoration without transforming it into class I, thus ensuring a successful result. Graphical abstract: Image 1 Highlights: The bulk-fill composite provides a proper margin seal and internal fit. A single increment of bulk-fill composite allows to simplify the class II restoration. The snowplow procedure performs a valid option to front a class II restoration. The flowable bulk-fill composite enhances internal marginal adaptation. The combination of proposed methods performs a complete data on microleakage.